2010
DOI: 10.1038/onc.2010.27
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic lymphoma kinase activates the small GTPase Rap1 via the Rap1-specific GEF C3G in both neuroblastoma and PC12 cells

Abstract: Many different types of cancer originate from aberrant signaling from the anaplastic lymphoma kinase (ALK) receptor tyrosine kinase (RTK), arising through different translocation events and overexpression. Further, activating point mutations in the ALK domain have been recently reported in neuroblastoma. To characterize signaling in the context of the full-length receptor, we have examined whether ALK is able to activate Rap1 and contribute to differentiation/proliferation processes. We show that ALK activates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 83 publications
1
40
0
2
Order By: Relevance
“…These results were confirmed in clonally-derived PC12 cells, which inducibly express wild-type or mutant ALK, allowing comparison of the activity of these mutants in a controlled manner. 35,37 In agreement with our previous results we observed that PC12 cells expressing wild-type ALK displayed a fivefold increase in MYCNP-luciferase upon stimulation of ALK with mAb46 (Figure 1c). PC12 clones expressing ALK gain-of-function human ALK F1174S and mouse ALK R1279Q (which is equivalent to the human ALK R1275Q mutation), also increased the expression of the MYCNPluciferase reporter 2 --3 fold.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These results were confirmed in clonally-derived PC12 cells, which inducibly express wild-type or mutant ALK, allowing comparison of the activity of these mutants in a controlled manner. 35,37 In agreement with our previous results we observed that PC12 cells expressing wild-type ALK displayed a fivefold increase in MYCNP-luciferase upon stimulation of ALK with mAb46 (Figure 1c). PC12 clones expressing ALK gain-of-function human ALK F1174S and mouse ALK R1279Q (which is equivalent to the human ALK R1275Q mutation), also increased the expression of the MYCNPluciferase reporter 2 --3 fold.…”
Section: Resultssupporting
confidence: 92%
“…In addition, the PC12hALK wt cells were stimulated with 1 mg/ml of the activating mAb46 as indicated. 37,48,49 Cells were lysed in 120 ml cell culture lysis reagent (Promega, Madison, WI, USA), of which 20 ml were used for luciferase assay according to manufacturer's protocol (Promega). Samples were measured in a TD-20/20 turner design luminometer (Turner Designs, Sunnyvale, CA, USA).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations